A - B = A + (-B) A - B = A + (-B) A - B = A + (-B) A - B = A + (-B)
The expression (a+b) + (a-b) can be rewritten as a + b + a - b = 2a.There is no need to use absolute value.
The fundamental theorum of calculus states that a definite integral from a to b is equivalent to the antiderivative's expression of b minus the antiderivative expression of a.
9aaaabbbb = 9 a^4 b^4
When factored it is: 12(A+b)
a + bc + d
it think ot is 5(a+b)
6a²b - 12ab²
34 is an equivalent expression.
You can use the ternary operator, in an expression such as: result = a > b ? a : b; This is equivalent to: if (a > b) result = a; else result = b;
The expression "-b".
Boolean Expression: Not A and Not B (Not A + Not B)
The expression 9+5 is equivalent.
A verbal expression for 5 a-b is that it is 5 is multiplied by the difference between a and b.
The value of a + b depends on the values of the individual variables.The expression a + b cannot be simplified.
b + 1 is b plus 1 as an algebraic expression.
The answer is b+1. Therefore the algebraic expression for this is b+1
If an algebraic expression is equivalent to another algebraic expression then it is an equation.
b-4 expression example b = 10 so b-4 = 6
If the algebraic expression can be written in the form of a(x)/b(x) where a(x) and b(x) are polynomial functions of x and b(x) â‰ 0, then the expression is a rational algebraic expression.
The equivalent expression of 10x-11x is -x, or negative x.